Effectiveness of a Community-Based Oral Cancer Screening Program Using Portable Fluorescence Spectroscopy in Rural Madhya Pradesh, India - Anuj Singh Parihar; Mahendrakumar A. Chaudhari; Hiren H. Patadiya; Jitender Kumar; Sanja Samir Sahu; Rashmi Laddha; Megha C Patel (Journal of Pharmacy and Bioallied Sciences)
Background: India continues to face the pressing problem of oral cancer, especially among the rural population, which has inadequate healthcare facilities. Like every other type of cancer, oral cancer can be treated successfully if diagnosed at an early stage. This study evaluates the effectiveness of a community-based oral cancer screening program employing portable fluorescence spectroscopy in rural Madhya Pradesh, India, with a focus on its feasibility and diagnostic accuracy in a resource-constrained setting. Methods: This cross-sectional study was conducted across 20 villages in rural Madhya Pradesh. Participants aged 30–65 years were recruited through community health camps and awareness campaigns, resulting in a total of 584 participants. Oral examinations were performed by trained healthcare workers, and any suspicious lesions were further evaluated using a portable fluorescence spectroscopy device. Histopathological diagnoses obtained through biopsies served as the gold standard for comparison. Results: The prevalence of oral potentially malignant disorders (OPMDs) was 12.8%, and the prevalence of oral cancer was 3.1%. Portable fluorescence spectroscopy demonstrated a sensitivity of 88.2% and specificity of 92.6% for detecting OPMDs. For oral cancer detection, the sensitivity was 90.0%, and the specificity was 94.1%. The positive predictive value was 78.9% for OPMDs and 82.4% for oral cancer, while the negative predictive value was 96.3% and 97.5%, respectively. Conclusions: This community-based oral cancer screening program using portable fluorescence spectroscopy proved to be a valuable tool for the early detection of oral cancer and OPMDs in a rural setting. The program has the potential to improve oral cancer management along with the device on account of its ease of use and portability, especially in low resource regions. In addition, the findings of this study suggest that such technologies can also be incorporated within existing community health initiatives, enhancing reach and facilitating timely treatment. Further research is warranted to assess the long-term impact of this screening program on oral cancer mortality and morbidity.